Selective excitotoxic lesions of the hippocampus and basolateral amygdala have dissociable effects on appetitive cue and place conditioning based on path integration in a novel Y-maze procedure. - Ito, R; Robbins, T; McNaughton, B; Everitt, B (2006)
The hippocampus and amygdala are thought to be functionally distinct components of different learning and memory systems. This functional dissociation has been particularly apparent in pavlovian fear conditioning, where the integrity of the hippocampus is necessary for contextual conditioning, and of the amygdala for discrete cue conditioning. Their respective roles in appetitive conditioning, however, remain equivocal mainly due to the lack of agreement concerning the operational definition of a 'context'. The present study used a novel procedure to measure appetitive conditioning to spatial context or to a discrete cue. Following selective excitotoxic lesions of the hippocampus (HPC) or basolateral amygdala (BLA), rats were initially trained to acquire discrete CS-sucrose conditioning in a Y-maze apparatus with three topographically identical chambers, the chambers discriminated only on the basis of path integration. The same group of animals then underwent 'place/contextual conditioning' where the CS presented in a chamber assigned as the positive chamber was paired with sucrose, but the same CS presented in either of the other two chambers was not. Thus, spatial context was the only cue that the animal could use to retrieve the value of the CS. HPC lesions impaired the acquisition of conditioned place preference but facilitated the acquisition of cue conditioning, while BLA lesions had the opposite effect, retarding the acquisition of cue conditioning but leaving the acquisition of conditioned place preference intact. Here we provide strong support for the notion that the HPC and BLA subserve complementary and competing roles in appetitive cue and contextual conditioning.